PENGARUH MOTIF PENGGUNAAN MEDIA ONLINE BOLA.NET TERHADAP KEPUASAN YANG DIPEROLEH MILANISTI INDONESIA SEZIONE PEKANBARU - Martius "; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Along with the development of technology, communication and information, it makes the development of the Internet, thereby encouraging the emergence of online media. One online media that is currently popular among football fans, ie online media Bola.net. Bola.net is an online media that explore all the actual information, textual and visual about national and international football. In the theory of Uses and Gratification audience basically using the mass media based on certain motives, where the media is considered trying to meet the needs of the audience called as an effective medium. The purpose of this study is to determine how much influence the use of online media Bola.net motive to satisfaction obtained Milanisti Indonesia Sezione Pekanbaru.The method used in this study is a quantitative method of explanation. Data collection techniques in this study using a questionnaire. The location of this research is in Milanisti Indonesia Sezione Pekanbaru. The number of samples for this study were 72 respondents. Sampling using accidental sampling technique. To determine how much influence these two variables, the researchers used a simple linear regression analysis. Questionnaire for data processing, carried out using the program Statistics Product And Service Solutions (SPSS) version of Windows 17.Results of research on the influence of online media usage patterns Bola.net to satisfaction obtained Milanisti Indonesia Sezione Pekanbaru, the regression coefficient values obtained in this study is Y = 2.744 + 0.027 X 0.03 significance level greater than α = 0.01. This means that there are no great influence among the motives Bola.net use online media to the satisfaction obtained Milanisti Indonesia Pekanbaru Sezione donation motive variables influence the use of the satisfaction of 11.8% and categorized as very weak effect. The percentages indicate that satisfaction can be achieved not exceed the expectations of motif usage. Thus H0 and Ha rejected.Keywords: Motive of Use Media, Bola.net, Obtained Satisfaction, Milanisti Indonesia Sezione Pekanbaru